Indeks Pembangunan Manusia dan Total Aset Terhadap Kondisi Ekonomi Masyarakat - Hurian Kamela; Thomson Sitompul; Erni Yulianti; Devi Mulyanti; Hendri Kartika Andri (Universitas Tangerang Raya, 2022)
There is still limited research on the development of local government conditions, namely economic development in the province. The measurement of the economic condition of the community uses the Human Development Index (HDI) score from the Central Statistics Agency (BPS). The purpose of this study is to provide empirical evidence regarding the relationship between HDI, total assets and the economic condition of the community. The study was based on a sample of 69 cities and regencies in 3 provinces, namely Aceh, North Sumatra and West Sumatra. The reason this sample is studied is to provide a comparison of economic conditions that occurred in 2016. The research method uses regression. The dependent variable is Economic Condition. The independent variables are the Human Development Index (HDI) and total assets. The results of the study are (1) HDI does not affect the economic condition of the community, (2) Total assets have an effect on the economic condition of the community. These results provide an explanation that the Human Development Index (HDI) is not all related to the economic welfare of a region, when the HDI is high it means that the economic capacity is not necessarily considered to be improving, while the number of assets owned by the City/Regency affects the economic condition of the community. The research contribution is to provide empirical evidence that the economic condition of a region does not depend on the progress of the region, but in accordance with the welfare conditions of each region.